Static frictional resistances of polycrystalline ceramic brackets with metal slot inserts - Rajakulendran Janahan; Jones Steven (Sciendo, 2023)
To compare the static frictional resistances of polycrystalline ceramic brackets with a gold slot insert (Desire), a stainless steel slot insert (Clarity), a conventional polycrystalline ceramic bracket (Transcend 6000) and a stainless steel bracket (Ultratrimm).